Functional characterization and correlation analysis of phenylalanine ammonia-lyase (PAL) in coumarin biosynthesis from Peucedanum praeruptorum Dunn. (February 2019) - Sui, Ziwei; Luo, Jun; Yao, Ruolan; Huang, Chuanlong; Zhao, Yucheng; Kong, Lingyi
Abstract: Coumarins exhibit many biological activities and are the main specialised metabolites of Peucedanum praeruptorum Dunn, an important plant used in traditional Chinese medicine. In preliminary studies, we cloned several genes involved in coumarin biosynthesis in P. praeruptorum, such as 4-coumarate: CoA ligase (4CL), p -coumaroyl CoA 2′-hydroxylase (C2′H), feruloyl CoA 6′-hydroxylase (F6′H) and bergaptol O -methyltransferase (BMT). However, phenylalanine ammonia-lyase (PAL) in P. praeruptorum ( PpPAL ) has not yet been studied. In the present study, we cloned one novel PpPAL gene. Subsequently, the relationship between gene and compounds was studied using quantitative real-time PCR (qRT-PCR) and High Performance Liquid Chromatography (HPLC) analysis. Then, enzyme function was analyzed withL -phenylalanine (L -Phe) as substrate. These experiments showed that the coumarin content could be upregulated by methyl jasmonate (MeJA), UV irradiation and cold, which was consistent with increased expression levels of PpPAL . In addition, correlation analysis indicated that coumarins were partially related to PpPAL . And the recombinant protein could catalyze the conversion ofL -Phe to trans -cinnamic acid ( t -CA) with a K m of 120 ± 33 μM and a K cat of 117 ± 32 min −1 . Besides, Tyr110, Phe116, Gly117, Ser206, Leu209, Leu259, Tyr354, Arg357, Asn387 and Phe403 were essential for enzymatic activity based on three-dimensional modeling and site-directed mutagenesis experiments. Altogether these results highlight the importance of PpPAL in abiotically induced coumarin biosynthesis and provide further insights regarding the structure-function relationships of this protein. Graphical abstract: Highlights: The coumarin content was partially related to Phenylalanine ammonia-lyase (PAL) gene expression. PAL gene regulation can impact on the whole coumarin pathway in Peucedanum praeruptorum. Ten residues in PAL were identified as essential for catalytic activity.